A Novel Approach for Achieving Low Young's Modulus in Ti-Based Metallic Glasses. Issue 1 (29th January 2019) - Luo, Jia-Peng; Jia, Xiao; Zheng, Dong-Lai; Wang, Gang; Sun, Jian-Fei; Yan, Ming
Abstract : Developing low-modulus Ti-based metallic glasses is of both scientific and practical interest. In this paper, we have analysed more than 40 different types of Ti-based metallic glasses and introduced two modified parameters that are based on a molecular orbital approach but are better in the prediction of Young's modulus of metal implants which should be about 30 MPa. Alloying elements are categorized and compared accordingly; Zr, Hf, Nb, Ta, Sn and Mo are proposed to be effective in designing low Young's modulus biomedical Ti-based metallic glasses.